2008
DOI: 10.1177/0272431608324473
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of Negative Peer Influence on Early Adolescent Externalizing Behaviors

Abstract: This study examined the extent to which antisocial behavior, parenting, and school connectedness moderated the association between peer deviancy in preadolescence and externalizing problems in early adolescence. The participants included 500 boys and girls, most of them African Americans. Peer deviancy was measured with teacher reports of aggressive-disruptive behavior for classmates identified by target children as friends. Parents provided information on parenting practices (nurturance and harsh and inconsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 52 publications
2
39
0
Order By: Relevance
“…A longitudinal study by Mrug & Windle (2009), did not support a moderating role of school connectedness (using five items from the School Connectedness Scale) on the link between teacher-reported peer deviance in grade five and target externalizing behaviors, including substance use, two years later. In this study, school connectedness was correlated with both the predictor (i.e., earlier teacher-reported peer deviance) and the outcome (later targets' substance use) variables, suggesting that mediation rather than moderation could be more appropriate in this case.…”
Section: Longitudinal Evidencementioning
confidence: 90%
See 1 more Smart Citation
“…A longitudinal study by Mrug & Windle (2009), did not support a moderating role of school connectedness (using five items from the School Connectedness Scale) on the link between teacher-reported peer deviance in grade five and target externalizing behaviors, including substance use, two years later. In this study, school connectedness was correlated with both the predictor (i.e., earlier teacher-reported peer deviance) and the outcome (later targets' substance use) variables, suggesting that mediation rather than moderation could be more appropriate in this case.…”
Section: Longitudinal Evidencementioning
confidence: 90%
“…Only two studies suggested that peer association may be greater in male as opposed to female adolescents who associate with delinquent and substance-using peers, as reported by teachers (Mrug & Windle, 2009) or the targets (Clark, Belgrave & Abell, 2012), and one study suggested that peer association may be greater in female adolescents associating with peers that use alcohol (Anderson, et al, 2011). In this last study though, a significant three-way interaction between gender, anxiety and peer association was found: highly anxious boys who had alcohol using friends reported the highest binge drinking rates in the last month.…”
Section: Cross-sectional Evidencementioning
confidence: 99%
“…Compared to the large number of studies exploring the moderating effect of family variables on the relationship between deviant peer association and delinquency (e.g., Coombs, Paulson, & Richardson, 1991;Farrell, Henry, Mays, & Schoeny, 2011;Galambos, Barker, & Almeida, 2003;Keenan et al, 1995;Lansford et al, 2003;Mason, Cauce, Gonzales, & Hiraga, 1994;Mrug & Windle, 2009;Poole & Regoli, 1979;Trucco, Colder, & Wieczorek, 2011;Vitario, Brendgen, & Tremblay, 2000;Warr, 1993;Zimmerman, Steinman, & Rowe, 1998), few have studied the moderating role of family functioning. Family functioning can be defined as "the quality of family life at the systemic level, such as wellness, competence, strengths, and weaknesses of a family" (Shek, 2005: p. 518).To the knowledge of the investigators, only one study conducted by Henry, Tolan, and Gorman-Smith (2001) adopted a composite score of family relationship (i.e., cohesion, communication, belief about family, shared deviant beliefs, support, and organization) and parenting practices (i.e., positive parenting, discipline effectiveness, discipline avoidance, monitoring/involvement) to investigate four possible models about the relationships among family functioning, peers and delinquency among 246 male adolescents.…”
Section: Family Functioning Deviant Peer Association and Delinquent mentioning
confidence: 99%
“…Several researchers have explored the moderating effect of family variables on the relationship between deviant peer association and delinquency, and have made mixed results (e.g., Coombs, Paulson, & Richardson, 1991;Farrell, Henry, Mays, & Schoeny, 2011;Galambos, Barker, & Almeida, 2003;Keenan et al, 1995;Lansford et al, 2003;Mason, Cauce, Gonzales, & Hiraga, 1994;Mrug & Windle, 2009;Poole & Regoli, 1979;Trucco, Colder, & Wieczorek, 2011;Vitario, Brendgen, & Tremblay, 2000;Warr, 1993;Zimmerman, Steinman, & Rowe, 1998). It remains unclear whether the buffering effect of family functioning exists or not, as few studies have examined family at a systemic level.…”
Section: Introductionmentioning
confidence: 99%
“…More recently research suggests that peer infl uences may shape the development and expression of deviance. Parenting and the family environment mediate the risk factors in relation to self-regulation as well as peer selection 33 . Developmental trajectories have been documented to explain the infl uence of ineffi cient parenting, poor childhood behaviours, peer rejection and further into adolescent externalising and internalising behaviors 34 .Inability to regulate impulsive behaviour combined with poor parenting techniques and experiences of rejection may lead to ineffective peer bonding in early childhood 35 .…”
Section: Peers and The Developing Adolescentmentioning
confidence: 99%